Lessons Learned from Japan for Disaster Risk Reduction to Build Disaster Resilience and Sustainable Communities During and Post-Covid-19 Pandemic - Sukmawati, Penta; Widana, I Dewa Ketut Kerta; Nurrobi, RM Tjahja; Widyaningrum, Nrangwesthi; Mayori, Ersha (Technium Social Sciences Journal, 2022)
Geologically, Indonesia and Japan have something in common, namely that they are crossed by the Eurasian and Pacific tectonic plate paths. According to data from the United States Geological Survey (USGS), Japan and Indonesia are the country most frequently experiencing disasters. What distinguishes Indonesia and Japan is the disaster management, both disaster management technology and the mitigation actions taken. Disaster management is one of the issues raised in the sustainable development goals. In every disaster that occurs, it is also hoped that the community/country will quickly recover and rise again in repairing the damage caused by the disaster. In this case, community resilience is a fundamental thing that must be done by all countries to ensure that every citizen can cope, anticipate, and can also recover after a disaster occurs. The aim of this study is to analyze disaster risk reduction and community resilience to disasters to continue development during the pandemic and after the pandemic: Lesson learned from Japan. This research data analysis uses qualitative data analysis techniques Miles, Huberman and Saldana. This data analysis technique consists of three components, namely data condensation, data presentation, and conclusion/verification withdrawal. The research results from the lessons learned that can be taken for Indonesia are: disaster risk reduction in Japan is carried out by utilizing innovative disaster mitigation technology and advanced early warning systems, public awareness of high disaster risk reduction, and Government policies that can encourage research and investment in technology development to reduce disaster risk and increase community resilience in the face of disasters.